The Influence of Lifestyle, Product Feature and Price on Consumer Satisfaction through Purchasing Decisions as an Intervening Variable (For iPhone Smartphone Users in Malang City) - Nuriati Nuriati; M. Agus Salim; Eka Farida (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The research objective was to determine the direct and indirect effects of lifestyle, product features and prices on consumer satisfaction through purchasing decisions as an intervening variable (on iPhone smartphone users in Malang). This research is a type of explanatory research using a quantitative approach. The population in this study is the people in Malang City who use an unknown number of iPhone Smartphones with a research sample of 90 respondents using the non-probability sampling technique, namely snowball sampling. Data analysis testing was carried out using the PLS (Partial Least Square) application. The results of the study show that there is no influence between lifestyle and purchasing decisions. Lifestyle has no effect on consumer satisfaction. Price has no effect on consumer satisfaction. Product features and prices have a significant effect on purchasing decisions. Product features and purchasing decisions have a significant effect on consumer satisfaction. Lifestyle does not affect consumers through purchasing decisions. Product features and price have a significant effect on consumer satisfaction which is mediated by purchasing decisions. Suggestions for future researchers are expected to add research samples to get maximum results or choose different objects and be able to replace existing variables such as loyalty, repurchase intention and social strata to provide a broad picture of the factors that influence purchasing decisions.